2019
DOI: 10.47878/hansenologia.2019.v44.34079
|View full text |Cite
|
Sign up to set email alerts
|

Padrões Espaciais Dos Casos Novos De Hanseníase Em Menores 15 Anos No Estado De Pernambuco, Brasil

Abstract: .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
1
0
6

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 0 publications
3
1
0
6
Order By: Relevance
“…The case detection rate in children under 15 years of age identified clusters of the high-high type with the Moran Map in the metropolitan region, indicating the presence of leprosy and its recent transmission force with active transmission foci in the family or among contacts 23 . The identification of the main highly endemic clusters in the metropolitan region corroborates the findings of another study 24 , thus confirming the urban nature of the endemic disease 14 , considering that the process of urbanization and geographic expansion can help in the circulation and maintenance of leprosy in the region 25 .…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The case detection rate in children under 15 years of age identified clusters of the high-high type with the Moran Map in the metropolitan region, indicating the presence of leprosy and its recent transmission force with active transmission foci in the family or among contacts 23 . The identification of the main highly endemic clusters in the metropolitan region corroborates the findings of another study 24 , thus confirming the urban nature of the endemic disease 14 , considering that the process of urbanization and geographic expansion can help in the circulation and maintenance of leprosy in the region 25 .…”
Section: Discussionsupporting
confidence: 84%
“…In this research, it was observed that the patterns of leprosy in the period studied showed significant spatial heterogeneity, with high endemicity in Pernambuco and variations in the detection coefficient between municipalities, with some being hyperendemic 14 . It is also noted the proximity of municipalities with high leprosy detection rates to those with low rates.…”
Section: Discussionmentioning
confidence: 80%
“…É o caso de pesquisas sobre a hanseníase que, ao se utilizarem do método bayesiano empírico local, alcançaram melhor compreensão das implicações espaciais devidas aos casos de municípios vizinhos, visualização do padrão espacial da doença, dos locais de risco e da influência de pequenas populações. 17,[20][21][22][23] Neste estudo, a análise da autocorrelação dos coeficientes suavizados possibilitou indicadores de incidência mais estáveis e a identificação de aglomerados de áreas mais críticas, abrangendo mais da metade dos municípios do estado, com clusters mais definidos na Zona da Mata e no Agreste paraibano. Este cenário reflete o quão grave se apresenta a tuberculose no estado, considerando-se que a área de casos de tuberculose na infância denota a transmissão recente da doença.…”
Section: Discussionunclassified
“…Este achado demonstrou a associação espacial nessas áreas, e corroborou achados de outras investigações que utilizaram o índice de Moran I e encontraram áreas de autocorrelação espacial e clusters de transmissão ativa, evidenciados pelo Moran Map, identificando locais prioritários para o controle da doença. 17,20,21 As possíveis limitações da pesquisa podem estar relacionadas ao uso de dados secundários do Sinan. Muito embora sejam dados oficiais, amplamente utilizados em trabalhos técnicos e científicos, estão sujeitos a inconsistências na quantidade, qualidade e processamento das informações.…”
Section: Discussionunclassified
See 1 more Smart Citation